2020
DOI: 10.1111/jpi.12643
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects the retina from experimental nonexudative age‐related macular degeneration in mice

Abstract: Nonexudative age‐related macular degeneration (NE‐AMD) represents the leading cause of blindness in the elderly. Currently, there are no available treatments for NE‐AMD. We have developed a NE‐AMD model induced by superior cervical ganglionectomy (SCGx) in C57BL/6J mice, which reproduces the disease hallmarks. Several lines of evidence strongly support the involvement of oxidative stress in NE‐AMD‐induced retinal pigment epithelium (RPE) and outer retina damage. Melatonin is a proven and safe antioxidant. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…However, its role in sleepdisorder regulation could be used as coadjutant treatment of ocular surface diseases due to the improvement in sleep disorders. In the posterior pole of the eye, the effect of circadian rhythm is not clear but melatonin properties such as antioxidant and antiangiogenic effects could be important to enhance other main treatments for AMD or other retinal diseases [94,[160][161][162].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its role in sleepdisorder regulation could be used as coadjutant treatment of ocular surface diseases due to the improvement in sleep disorders. In the posterior pole of the eye, the effect of circadian rhythm is not clear but melatonin properties such as antioxidant and antiangiogenic effects could be important to enhance other main treatments for AMD or other retinal diseases [94,[160][161][162].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the therapeutic use of melatonin in AMD, different studies confirmed its antioxidant and antiangiogenic properties, which provide a protective effect on photoreceptors and retinal pigment epithelium against oxidative stress, apoptosis, and mitochondrial DNA damage [94,[160][161][162].…”
Section: Retinal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent epidemiology has established that diabetics treated with the drug metformin are at notably lower risk for AMD than other diabetics that are comparably controlled; this could reflect a protective role for AMPK in this syndrome [225,226]. Urinary levels of the melatonin metabolite 6-sulfatoxymelatonin have been reported to be low in patients with AMD, and melatonin administration is protective in a mouse model of dry AMD [227][228][229][230]. Although the decreased risk for AMD associated with frequent spinach ingestion has been attributed to lutein, little attention has been paid to the fact that spinach is extraordinarily rich in betaine, and also a fine source of folate.…”
Section: Pertinence To Dry Macular Degenerationmentioning
confidence: 99%
“…In an experimental model of nonexudative AMD in mice induced by superior cervical ganglionectomy (SCG), melatonin administered as subcutaneous pellets, was capable to significantly preserve visual functions as well as RPE and outer retinal structure, and also prevented the increase of oxidative stress markers. These results were observed when the melatonin treatment was started both at 48 h and 4 weeks post-SCG, which means that melatonin could not only prevent, but also slow or reverse nonexudative-AMD progression [ 206 ]. On a photoreceptor degeneration mice model induced by an intraperitoneal administration of N-methyl-N-nitrosourea (MNU), melatonin was injected into the vitreous body, and was able to ameliorate effectively the MNU induced photoreceptor degeneration and also improved the visual signal transmission within inner retinal circuits by inhibiting apoptosis and mitigating oxidative stress [ 207 ].…”
Section: New Therapeutics For Amdmentioning
confidence: 99%